2005
DOI: 10.1017/s0025315405010933h
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and growth of the hermit crab Pagurus brevidactylus (Anomura: Paguridae) from the northern coast of São Paulo, Brazil

Abstract: The hermit crab Pagurus brevidactylus (Crustacea: Anomura: Paguridea) from the infralittoral area of Anchieta Island, Ubatuba, was characterized by population structure (size, sex ratio, reproduction and recruitment) and growth. Animals were collected monthly during 1999 by SCUBA diving. A total of 1525 individuals was collected (633 males and 892 females), 695 of them were ovigerous females. Overall sex ratio was 0.7:1 in favour of females. The crabs showed a unimodal distribution with males signi¢cantly larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 3 publications
(4 reference statements)
6
20
1
2
Order By: Relevance
“…Catapaguroides microps is sexually dimorphic in relation to size, with males reaching larger shield lengths than females. A similar growth pattern has been observed in populations of shallow water hermitcrabs such as those of Calcinus tibicen (FRANSOZO; MANTELATTO, 1998), Dardanus insignis (BRANCO et al, 2002), and Pagurus brevidactylus (MANTELATTO et al, 2005) studied in São Paulo, and Diogenes puligator (MAJÓN-CABEZA; GARCIA-RASO, 1998) in the Strait of Gibraltar. Above the 2.2 mm CS, males become more abundant (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Catapaguroides microps is sexually dimorphic in relation to size, with males reaching larger shield lengths than females. A similar growth pattern has been observed in populations of shallow water hermitcrabs such as those of Calcinus tibicen (FRANSOZO; MANTELATTO, 1998), Dardanus insignis (BRANCO et al, 2002), and Pagurus brevidactylus (MANTELATTO et al, 2005) studied in São Paulo, and Diogenes puligator (MAJÓN-CABEZA; GARCIA-RASO, 1998) in the Strait of Gibraltar. Above the 2.2 mm CS, males become more abundant (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The occupation of the largest shells by the males has been reported in other studies Mantelatto and Meireles 2004), and this occurs as a function of the size difference attained by the different sexes, as the males' investment on reproduction is lower than for females. Male Pagurus exilis attained larger sizes than females, evidencing sexual size dimorphism (Espósito et al forthcoming) as reported for Pagurus species such as P. criniticornis, P. brevidactylus, P. excavatus (Herbst, 1791), and P. filholi (De Man, 1887) (Faria 2004;Mantelatto et al 2005;Macpherson and Raventos 2004;Goshima et al 1998, respectively).…”
Section: Discussionmentioning
confidence: 64%
“…Amostragens periódicas viabilizariam afirmações mais fidedignas quanto aos padrões populacionais das diferentes espécies. Com efeito, os machos atingem tamanhos maiores que as fêmeas [e. g. Clibanarius vittatus (Bosc, 1802) (REIGADA & SANTOS, 1997), Paguristes erythrops Holthuis, 1959(GARCIA & MANTELATTO, 2001, Calcinus tibicen (Herbst, 1791) (FRANSOZO et al, 2003), Pagurus brevidactylus (Stimpson, 1859) (MANTELATTO et al, 2005)] o que parece ser um padrão usual entre os ermitões da costa brasileira.…”
Section: Discussionunclassified